A Discovery of Relevant Hepatoprotective Effects and Underlying Mechanisms of Dietary Clostridium butyricum Against Corticosterone-Induced Liver Injury in Pekin Ducks - Liu, Yanhan; Liu, Cun; Huang, Liqing; Xia, Zhaofei (Microorganisms (Basel), 2019)
Clostridium butyricum (C. butyricum) can attenuate oxidative stress, inflammation, and hepatic fatty deposition in poultry, however, the underlying mechanisms for this in Pekin ducks remain unclear. This study evaluated these hepatoprotective effects and the underlying mechanisms in a corticosterone (CORT)-induced liver injury model in Pekin ducks fed a C. butyricum intervention diet. A total of 500 Pekin ducks were randomly divided into five groups: one group (CON group) was only provided with a basal diet, three groups were provided a basal diet with 200 mg/kg (LCB group), 400 mg/kg (MCB group), or 600 mg/kg (HCB group) C. butyricum, respectively, and one group was provided a basal diet with 150 mg/kg aureomycin (ANT group) for 42 d. At 37 days-old, all ducks received daily intraperitoneal injections of CORT for five days to establish a liver injury model. C. butyricum intervention alleviated liver injury by decreasing the liver organ indices, hepatic steatosis and hepatocyte necrosis, and improving liver function, antioxidant capacity, and inflammatory factors. Hepatic RNA-seq revealed 365 differentially expressed genes (DEGs) between the MCB and CON groups, with 229 up- and 136 down-regulated DEGs in the MCB group. Between the MCB and ANT groups, 407 DEGs were identified, including 299 up- and 108 down-regulated genes in MCB group. Some DEGs in the MCB group related to oxidative stress and inflammatory responses such as Sod3, Tlr2a/b, and Il10, which were up-regulated, while Apoa1, Cyp7a1, Acsl1/5, Fasn, Ppar-γ, and Scd, which are involved in lipid metabolism, were down-regulated, indicating that these genes were responsive to dietary C. butyricum for the alleviation of corticosterone-induced hepatic injury. Toll-like receptor signaling, PI3K-Akt signaling pathway, cytokine-cytokine receptor interaction, peroxisome proliferator-activated receptor (PPAR) signaling pathway, adipocytokine and glycerophospholipid metabolism signaling pathway were significantly enriched in the MCB group. These findings indicate that C. butyricum intervention can protect Pekin ducks from corticosterone-induced liver injury by the modulation of immunoregulatory- and lipid metabolism-related genes and pathways.